Bibliometric Analysis of Computational Mapping in The Publication of Nano Propolis using VOSviewer - Alifia Vidiashtari Nabilla; Asep Bayu Dani Nandiyanto (Advance Sustainable Science Engineering and Technology, 2022)
Previous research has shown that propolis contains natural ingredients such as antibacterial, antifungal and anti-inflammatory activities. With a lot of content and benefits for health, further research is needed on nanoparticles in propolis. This research was conducted to determine the development of studies on nano propolis in the last 10 years. The data used in this study comes from indexed articles that have been published on Google Scholar. The software used for data processing is Publish or Perish for data filtering and VOSviewer for visualization of bibliometric computational. The results showed that there were 1000 articles that matched the criteria, and it was found that nano propolis is divided into 3 main fields, namely nanoparticles, propoli, and propolis. Based on data mapping, it can be seen that there is an increase in research on nanopropolis around 2019-2020. This review can be a starting point for further research related to nanopropolis.